The Effect of Curing Process on Oil Palm Empty Fruit Bunch Fibre Cement Board Performance and Microstructure Appearance - Saiful Adli; Nik Mohd Zaini Nik Soh (Journal of Structural Monitoring and Built Environment, 2026)
This research investigates the potential of utilizing oil palm empty fruit bunch (EFB) fibres as sustainable materials for construction, addressing both environmental and industrial challenges associated with waste management in the palm oil industry. EFB fibres were processed through filtering to remove impurities, sun-drying to reduce moisture content, and hot water treatment at 100°C for 2 hours. These fibres were fabricated into cement boards (EFBCB) with a cement-to-fibre ratio of 3.5:1 and a target density of 1,300 kg/m³. The study examined the physical and mechanical properties of EFBCB across curing durations of 7, 14, and 28 days. Results for 7-day curing indicated moderate density and mechanical performance due to partial hydration. At 14 days, increased moisture evaporation and fibre bonding improved mechanical properties but revealed early microcracking. By 28 days, prolonged curing led to further porosity, reduced density, and microstructural degradation, impacting dimensional stability and mechanical integrity. Microstructural analysis using Scanning Electron Microscopy (SEM) highlighted the evolving fibre-matrix interactions across curing periods. These findings emphasize the potential of EFB fibres as eco-friendly construction materials and the need to optimize curing durations for enhanced performance.